2016
DOI: 10.1037/a0039715
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol reactions during family conflict discussions: Influences of wives’ and husbands’ exposure to family-of-origin aggression.

Abstract: Objective Though family-of-origin aggression (FOA) is a known risk for later emotional and physical problems in adulthood, little is known about how early exposure to aggression influences physiological reactivity in the domain-specific context of family conflict experienced as an adult. This study investigates whether report of FOA influences spouses’ hypothalamic-pituitary-adrenal (HPA) axis responses during conflict discussions with their family-of-procreation and also whether current hostilities, observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 43 publications
6
31
0
3
Order By: Relevance
“…As with the variability seen in research on physiological regulation, exposure to family aggression was associated with both heightened and dampened physiology. Consistent with allostatic theory , heightened physiology was more evident when the challenging interpersonal situation was somewhat novel (e.g., involving a friend; , or a romantic partner; ), as contrasted with attenuated physiology when recreating repeating family battles (e.g., adolescents engaged in conflicts with their parents; ). Heightened physiological reactivity in emotionally charged situations with salient others presumptively supports conflict sensitization in individuals who have been exposed to violence.…”
Section: Conclusion and Next Stepsmentioning
confidence: 63%
See 1 more Smart Citation
“…As with the variability seen in research on physiological regulation, exposure to family aggression was associated with both heightened and dampened physiology. Consistent with allostatic theory , heightened physiology was more evident when the challenging interpersonal situation was somewhat novel (e.g., involving a friend; , or a romantic partner; ), as contrasted with attenuated physiology when recreating repeating family battles (e.g., adolescents engaged in conflicts with their parents; ). Heightened physiological reactivity in emotionally charged situations with salient others presumptively supports conflict sensitization in individuals who have been exposed to violence.…”
Section: Conclusion and Next Stepsmentioning
confidence: 63%
“…In a study of maternal sensitivity during childhood, less sensitive caregiving was prospectively linked with greater increases in electrodermal activity during arguments with romantic partners, even controlling for relationship quality and socioeconomic factors . In another study, wives' retrospective reports of aggression in their families of origin related to their own and their husbands' heightened cortisol activity during an argument, which we interpreted as enhanced risk detection . In addition, current interpersonal experiences apparently interacted with adverse family history in regulating physiology: The combination of family‐of‐origin aggression with partners' observed hostility during the argument moderated the direct effect of family‐of‐origin aggression—husbands' cortisol was heightened, whereas wives' cortisol was attenuated, perhaps signaling disengagement from aversive discussions with partners.…”
Section: Development and Physiological Processesmentioning
confidence: 80%
“…As compared to marital aggression, which is recent or even ongoing, FOA occurred decades ago and is unrelated to the reports of marital aggression. In another paper with this same sample (Arbel et al, 2015), wives’ FOA also was linked to greater cortisol activity in a conflict discussion with their spouse and adolescent child, which led to our speculation that women's early experiences hold more relevance in future stressful interpersonal situations. This, of course, needs to be replicated in other samples but does suggest that FOA may influence the interpretation of interpersonal stress.…”
Section: Discussionmentioning
confidence: 90%
“…In a measure designed for the larger study, husbands and wives separately reported on their exposure to FOA before the age of 18 (see Arbel, Rodriguez, & Margolin, 2015). Items assessed parent-to-child and interparental verbal and physical aggression on a 7-point scale, ranging from 0 ( never ) to 6 ( more than 50 times ).…”
Section: Methodsmentioning
confidence: 99%
“…This pattern of stress reactivity can be life‐course persistent and has been shown to be present in intimate partners in conflict. Arbel, Rodriguez, and Margolin () found elevated cortisol levels in men arising from an interaction between exposure to family of origin violence and current partner hostility.…”
Section: Early‐life Risk For Family‐only Domestic Violence Perpetratimentioning
confidence: 99%